The British Policy of Indirect Rule in India: A Historical Perspective - Sarkar, Anil Kumar (TAWARIKH, 2014)
ABSTRACT: When the British established a vast empire in Asia and Africa, they faced the basic problem, because they dominated over the existing political authorities.In most parts of their dominions, they had adopted a system of utilizing the pre-existing political authority, indigenous rulers or traditional chiefs, to carry out most of the processes of local government. This was the situation where an imperial power did not supersede the pre-existing political authority, but established its dominance over it, where traditional rulers were allowed to exercise as before in the local governance. This system is called âIndirect Ruleâ, which stood for a Government through the pre-existing political authority. This was a well-established system of British colonial administration and was followed in Africa, Malaya States, and elsewhere. The British system of indirect rule was the exercise of determinative influence and exclusive political control over a nominally sovereign State, a control recognized by both sides. Under it, the administration of native State continued to exist under the aegis of the imperial power. But the traditional rulers, who continued to rule under the domination of the imperial power, had lost their independence and were subject to supervision and owed allegiance to the imperial authority. Under such conditions, the district Officers and Residents became the guardians of their power and authority. Not surprisingly, these local authorities came to be identified with the interests of the British. In fact, the British system of indirect rule was motivated by the basic principles of governing a large territory with minimum expenditure.KEY WORDS: Dominions, indigenous, local governance, indirect rule, sovereign state, imperial power,Â  Residents, and British and India.About the Author: Dr. Anil Kumar Sarkar is an Assistant Professor in History at the ABN (Acharya Brojendra Nath) Seal College, Cooch Behar, West Bengal, India. For academic interests, he can be reached via his e-mail address at: sarkaranil71@yahoo.inHow to cite this article? Sarkar, Anil Kumar. (2014). âThe British Policy of Indirect Rule in India: A Historical Perspectiveâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.135-144. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 15, 2014); Revised (March 17, 2014); and Published (April 28, 2014).